Superovulatory and embryonic response in alpacas according to the number of follicles recruited by follicular wave - Pozo C., Alfredo (2021)
The aim of this study was to evaluate the superovulatory and embryonic response in alpacas with equine chorionic gonadotropin (eCG) according to the number of follicles recruited >3 mm in the follicular wave (FW). Twenty-six alpacas from the CIP “Chuquibambilla”, Universidad Nacional del Altiplano, Puno, Peru, were selected and distributed into two experimental groups: GE01 (n=15 alpacas) with less than three follicles >3 mm and GE02 (n=11 alpacas) with more from four follicles >3 mm in diameter to follicular recruitment post-induction of ovulation by a follicle >7 mm with 0.0042 mg of buserelin acetate (BA). Both groups were evaluated by ultrasound every other day until the beginning of the third follicular wave. Subsequently, females with follicles >7 mm were induced to ovulate with BA (day 0), ovulation was verified at 36 h and 700 IU of eCG was administered. On day 6.5 animals were mated and 7.5 days later the embryos were collected. The superovulatory response was similar in GE01 and GE02 with 4.4 ± 4.0 and 4.7 ± 3.7 follicles between >3 and <7 mm; 7.5 ± 3.7 and 10.1 ± 6.3 follicles >7 mm; and 7.2 ± 3.3 and 8.6 ± 5.0 corpora lutea, respectively. Furthermore, GE01 and GE02 presented 1.6 ± 0.5 and 2.8 ± 1.3 luteinized anovulatory follicles and 2.0 ± 1.0 and 2.0 ± 2.2 anovulatory follicles, respectively. In 80% of alpacas in GE01 2.5 ± 1.4 embryos were collected and in 70% of alpacas in GE02 2.3 ± 1.1 embryos were collected. Likewise, 25 transferable and 5 non-transferable embryos were recovered in GE01 (n=15) and 12 transferable and 4 non-transferable embryos in GE02 (n=10). The results suggest that there is no difference in the ovarian response and embryonic collection in alpacas overstimulated with eCG despite a marked difference in emerging follicles >3 mm in the first FW and that it was not sustainable in the second and third FW.